2018
DOI: 10.3390/md16090322
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Polyphosphate Nanoparticles from a Marine Cyanobacterium Synechococcus sp. PCC 7002: Production, Characterization, and Anti-Inflammatory Properties In Vitro

Abstract: Probiotic-derived polyphosphates have attracted interest as potential therapeutic agents to improve intestinal health. The current study discovered the intracellular accumulation of polyphosphates in a marine cyanobacterium Synechococcus sp. PCC 7002 as nano-sized granules. The maximum accumulation of polyphosphates in Synechococcus sp. PCC 7002 was found at the late logarithmic growth phase when the medium contained 0.74 mM of KH2PO4, 11.76 mM of NaNO3, and 30.42 mM of Na2SO4. Biogenic polyphosphate nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…[14][15][16][17] A subsequent study also showed that polyphosphate produced by a marine cyanobacterium, Synechococcus, exerted an antiinflammatory function. 18 The present study identified the most suitable chain length of polyphosphate for the enhancement of the intestinal barrier function and confirmed the efficacy of long-chain polyphosphate in inflammation models (including a genetically induced mouse colitis model and inflammation-induced human macrophages). Furthermore, the safety of long-chain polyphosphate was confirmed by preclinical tests, and we conducted the first-in-human trial to determine the safety and efficacy of long-chain polyphosphate in patients with refractory UC.…”
supporting
confidence: 75%
“…[14][15][16][17] A subsequent study also showed that polyphosphate produced by a marine cyanobacterium, Synechococcus, exerted an antiinflammatory function. 18 The present study identified the most suitable chain length of polyphosphate for the enhancement of the intestinal barrier function and confirmed the efficacy of long-chain polyphosphate in inflammation models (including a genetically induced mouse colitis model and inflammation-induced human macrophages). Furthermore, the safety of long-chain polyphosphate was confirmed by preclinical tests, and we conducted the first-in-human trial to determine the safety and efficacy of long-chain polyphosphate in patients with refractory UC.…”
supporting
confidence: 75%
“…High levels of BPNPs were synthesized in Synechococcus sp PCC7002 overexpressing the the ppk gene. The isolated BPNPs from this cyanobacterium were shown to be taken up by polarized human intestinal epithelial (Caco-2) cells (Gao et al, 2018) where they inhibited the induction of nitric oxide synthase and the production of proinflammatory mediators in mouse cell cultures (Feng et al, 2018). This work on potential "health impacts" and uses of polyP for medical applications is intriguing, although it would benefit from further studies of the efficacy and scope of polyP in these processes.…”
Section: Polyp and Biotechnological Applicationsmentioning
confidence: 99%
“…This now includes promoter design, reporter proteins, selection strategies and overproduction protocols for recombinant protein expression ( Ludwig and Bryant, 2012 ; Ruffing et al, 2016 ). Promising applications for this cyanobacterial strain include its use to produce biogenic polyphosphate nanoparticles to treat and prevent inflammatory gastrointestinal diseases ( Feng et al, 2018a , b , 2019 ), and hyaluronic acid, a natural polymer with a broad range of cosmetic and biomedical applications ( Zhang et al, 2019 ). Other attractive Synechococcus strains, such as Synechococcus elongatus PCC 7942 and the more recently characterized Synechococcus elongatus UTEX 2973 ( Yu et al, 2015 ), are already being used for the synthesis of bioactive molecules such as heparosan, a pharmaceutical precursor of heparin, and glycosaminoglycans ( Sarnaik et al, 2019 ), including heparan sulfate, chondroitin sulfate and hyaluronic acid, which play key roles in tissue maintenance, repair and regeneration ( Melrose, 2016 ).…”
Section: Transgenic Photosynthetic Organismsmentioning
confidence: 99%